Analysis of trajectory and motion parameters of an industrial robot cooperating with a numerically controlled machine tools - Peta, Katarzyna; Wlodarczyk, Jan; Maniak, Mateusz (Journal of manufacturing processes, 2023)
The tendency to improve manufacturing processes also applies to robotic and automated processes. Optimization of the trajectory and motion parameters of an industrial robot is one of the most important aspects of effective production. Robots are often not independent mechanical units, but interact with other work machines. The effective cooperation of mechanical devices is a significant technological challenge. In this paper, the types of positioning, trajectories and motion parameters of an industrial robot cooperating with numerically controlled machine tools were analyzed. The considered example is the process of machining the riveting tool holder. The tasks of offline programming of numerically controlled machine tools and robots were combined. For this purpose, SinuTrain and RobotStudio software were used. The main simulation analyzes indicated the relationship between the programmable parameters of the robot's motion and the actual values of the speed and acceleration of the tool center point. In the paper, the influence of speed and positioning accuracy on the duration of the process were also indicated. The results of the analyzes allowed to optimize the working time of the robot while maintaining the appropriate quality of the process. [Display omitted]